Disseminated Cutaneous Tuberculosis like Fungal Sporotrichosis Successfully Treated With Terbinafine: A Rare Case Report - Gautam, Anil; Subedi, Bijay; Awasthi, Janak; Adhikari, Suman (Nepal Journal of Health Sciences, 2021)
Occurrence of Sporotrichosis is uncommon in Nepal. Here, we describe a case of cutaneous Sporotrichosis of 43 years old adult male working as a farmer from Pokhara-30, Nepal with unusual skin tuberculosis like presentation since 3 years, initiating from the unusual location in right pinna. Histopathological observation was suggestive of cutaneous tuberculosis, lupus vulgaris, cutaneous leishmaniasis due to overlapping findings during biopsy. The case was diagnosed by the pharmacological intervention observing the effect of drugs i.e., terbinafine. The purpose of reporting this serendipitous case is to enhance timely diagnosis, avoid the diagnostic dilemma for future references.